THE THE ERROR OF SOLVING COMPOSITION FUNCTION PROBLEM OF MADRASAH ALIYAH MUSLIMAT PALANGKA RAYA STUDENTS - sarjoko yohanes; Pancarita .; Qodri Ali Hasan; Syahri Ramadhan (JURNAL PENDIDIKAN, 2021)
Abstract The problem of difficulty in mastering the function composition material occurs at Madrasah Aliyah Muslimat Nahdlatul Ulama Palangka Raya. This study aims to describe student errors in solving function composition problems. Descriptive method was used to identify the errors of 45 students of class X Natural Sciences. Data were collected with 5 essay questions and in-depth interviews. The essay questions were validated by three assessors from teachers and lecturers of Mathematics Education, who stated that the essay questions were of good quality. The research procedure was carried out through the stages of giving an essay test to all students and in-depth interviews with three students. The results showed that: first, there was a factual error, where students grammatically wrote the facts in the questions incorrectly, concluded the answers incorrectly, made the wrong arrows on the function composition diagram. Second, misconceptions occur due to misunderstanding the types of functions and the terms of the composition of functions which causes incorrect answers to solve the problem of proving the composition of functions. Operational errors occur because students do not master algebraic arithmetic operations. Errors in principle occur, where students do not understand well the definition and properties of compositional functions.